Metrological complementarity reveals the Einstein-Podolsky-Rosen paradox - Benjamin Yadin; Matteo Fadel; Manuel Gessner (Nature Communications, 2021)
Steering reflects the ability to predict measurement results on one side of a quantum-correlated system based on measurements on the other side, which can be phrased as a metrology problem. Here, the authors explore this connection, deriving a general steering criterion based on quantum Fisher information.